2017
DOI: 10.1007/s00253-017-8307-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymers for enhanced oil recovery: fundamentals and selection criteria

Abstract: With a rising population, the demand for energy has increased over the years. As per the projections, both fossil fuel and renewables will remain as major energy source (678 quadrillion BTU) till 2030 with fossil fuel contributing 78% of total energy consumption. Hence, attempts are continuously made to make fossil fuel production more sustainable and cheaper. From the past 40 years, polymer flooding has been carried out in marginal oil fields and have proved to be successful in many cases. The common expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 78 publications
1
94
0
Order By: Relevance
“…Polymer flooding has been successful in Chinese oilfields [8,9], but the technique is not widely used worldwide. In fact, Rellegadla et al [10] recently reported that only about 10% of EOR projects worldwide use polymer flooding methods. Although the addition of polymeric materials improves the sweep efficiency through the reservoir, it can also cause pore plugging if an inappropriate polymeric material is selected for the application (or if the reservoir geology is not suitable for polymer flooding).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer flooding has been successful in Chinese oilfields [8,9], but the technique is not widely used worldwide. In fact, Rellegadla et al [10] recently reported that only about 10% of EOR projects worldwide use polymer flooding methods. Although the addition of polymeric materials improves the sweep efficiency through the reservoir, it can also cause pore plugging if an inappropriate polymeric material is selected for the application (or if the reservoir geology is not suitable for polymer flooding).…”
Section: Introductionmentioning
confidence: 99%
“…This is the common problem injected chemical fluids face in the oil field. For decades, polymers are known as viscosity enhancer and have shown promising results, but present various challenges in oil field such as thermal instability, adsorption, gelation, high cost and environmental concern (Rellegadla et al 2017;Speight 2016). However, recent EOR studies focus on nanoparticles (NPs) utilization to improve important properties such as interfacial tension, wettability alteration and viscosity due to their thermophysical properties (Koca et al 2017;Adenutsi et al 2018;Zallaghi et al 2018;Sharma and Sangwai 2017;Choi et al 2017;Kean Chuan et al 2016;Cheraghian et al 2015;Pozhar 2000;Hendraningrat et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer flooding has been carried out for the past 40 years in many marginal oil fields and its effectiveness has proved to be successful. The general expectation from polymer flooding is to obtain about 50% ultimate recovery with averagely 15 to 20% incremental recovery over secondary water flooding process [1]. Both naturally derived polymers like xanthan gum and synthetic polymers such as the partially hydrolysed polyacrylamide (HPAM) have been used basically for the purpose of viscosifying water for polymer flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the chemical cost of polymer flooding is a function of the polymer selected for flooding, xanthan's cost is stable when compared to the fluctuating cost of polyacrylamide polymer. The polyacrylamide is actually synthesised from petroleum products and their costs in the market are very sensitive to the crude oil prices [1]. Thus, there is need to synthesize less costly environmentally friendly polymers with high degree of stability as this is a sure way of generating more recovery while reducing cost.…”
Section: Introductionmentioning
confidence: 99%